White savior narrative vs. emerging identity in american sports films - Korzeniewska-Nowakowska, Paulina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article I strive to contribute to the discussion on sports white savior narratives and the portrayal of emerging cultural identity as shown in sports dramas. By examining selected movies, I argue that sports dramas extensively use the tropes of white savior narratives and, thus, offer biased understanding of the ethnic minorities` experience and their identity formation process in the United States.
Keywords: white savior; sport films; ethnical minorities; identity